Keteladanan Yesus sebagai Sumbangsih bagi Guru Pendidikan Agama Kristen - Irwansyah Putra Hondro (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
Jesus Christ as a role model for PAK teachers so that the role and competence of Christian Religious Education (PAK) teachers. Jesus, as the Great Teacher, provides a learning model centered on love, patience, wisdom, and real-life examples. By understanding and applying the principles of Jesus' leadership and teaching, PAK teachers can be more effective in guiding students, both in spiritual and moral aspects. This research uses a qualitative method with a descriptive-analytical approach. Data were collected through literature study of theological literature, Christian education, and analysis of Jesus' teachings and actions in the Bible. The results showed that the example of Jesus has a significant impact in shaping the character of PAK teachers, especially in the aspects of integrity, servant leadership, and the ability to educate with love and wisdom. The conclusion of this study confirms that PAK teachers who imitate Jesus can be agents of transformation in the world of education, forming a generation that is not only intellectually intelligent, but also has a strong Christian character.